Advances in understanding cis regulation of the plant gene with an emphasis on comparative genomics. (October 2015) - Burgess, Diane G; Xu, Jie; Freeling, Michael
Highlights: Chromatin accessibility and chromatin looping dynamically regulate transcription. Transcription factor binding is not equal to transcription factor function. The molecular genetics of the PIF quartet is highlighted as a focal case study. Complementary conserved noncoding lists are compared, evaluated, and merged. Transposons near genes may act as cis modifiers of baseline transcriptional power. Abstract : The plant gene model remains largely an extrapolation from animals, with the cis functional unit, the gene, cast as a dynamic looping structure. Molecular genetics with model plants continues to make advances; highlighted here are quantitative-occupancy results from the Arabidopsis thaliana (Arabidopsis) Phytochrome-Interacting bHLH transcription Factors (PIF) quartet. Compared to this complex snapshot, results from chromatin occupancy and other Encyclopedia of DNA Elements (ENCODE)-like approaches increase our transcription factor-motif cognate library, but regulation cannot by itself be inferred from binding. Complementary published Arabidopsis conserved noncoding sequence lists are compared, evaluated, merged, and released. Comparative genomic approaches have identified a cis modifier of a gene's expression — hypothetically, a transposon-based 'rheostat' — that works in all cells, times and places.